Control without Ownership: Nominee Agreements and the Restriction of Freehold Land Rights for Foreign Nationals in Indonesia - Farida Paroto; Ma'ruf Akib; Ismi Fadjriah Hamzah (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This article examines the legal status, doctrinal coherence, and regulatory implications of nominee agreements used to facilitate foreign control over freehold land in Indonesia. Although Indonesian agrarian law formally prohibits foreign ownership of freehold title, nominee arrangements continue to operate through private contractual mechanisms that separate formal ownership from effective control. Using normative legal research grounded in statutory, conceptual, and analytical approaches, this study analyzes the interaction between agrarian law, civil law doctrine, and regulatory policy. The findings demonstrate that nominee agreements occupy a structurally ambiguous position: while formally inconsistent with the prohibition regime and the social function principle of land, their persistence reflects deeper tensions between title-based formalism and the absence of a transparent beneficial ownership framework. The article argues that the endurance of nominee practices is not solely a consequence of weak enforcement, but of regulatory design limitations that fail to address sophisticated forms of legal circumvention. It concludes that reconstructing the regulatory approach, from an absolute prohibition model toward a transparency- and accountability-based framework, offers a more coherent strategy to reconcile agrarian sovereignty, legal certainty, and foreign investment dynamics. This reconstruction strengthens doctrinal integrity while enhancing regulatory effectiveness within Indonesia’s contemporary land law system.